Pengaruh Penerapan Model Project Based Flipped Classroom Learning Terhadap Hasil Belajar Akuntansi Keuangan - Arief, Hidayatul; Refnida, Refnida; Mayasari, Mayasari; Tersta, Friscilla Wulan (Universitas Negeri Surabaya, 2024)
This research aims to prove whether or not there is an influence from implementing the project based flipped classroom learning model on student learning outcomes in the introductory financial accounting course. This type of research uses a quasi-experimental research type with the matching-only posttest-only control group design. The subjects in this research were entry-level students at the Economics Education Study Program, Faculty of Teacher Training and Education, Jambi University. The data collection instruments in this research used test questions. The data analysis technique in this research uses descriptive data analysis techniques and comparative tests of two independent samples. This research obtained results that the average score of the experimental class was higher than the control class and based on the Mann Whitney U test, there was a significant difference between the scores of the experimental class and the control class, which can be concluded that there was an influence of the application of the project based flipped classroom learning model on the results students study in an introductory financial accounting course.